Negative pole piece and preparation method thereof, sodium ion battery and electric equipment
By adopting a multi-layer coating structure in the negative electrode sheet of the sodium ion battery and using the combination of hard carbon and soft carbon, the problems of high mechanical strength, low electronic conductivity and difficult to improve compaction density in sodium ion batteries are solved, and higher flexibility, compaction density and electronic conductivity are achieved, improving the overall performance of the battery.
Patent Information
- Application Number
- CN202411754083.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
AI Technical Summary
As the negative electrode material of sodium ion batteries, hard carbon has problems such as high mechanical strength, low electronic conductivity, difficulty in improving compaction density and easy powder loss, which affects the performance and life of the battery.
The first coating consisting of hard carbon, first soft carbon, first conductive agent, first dispersant and first binder and the second coating consisting of second soft carbon, second conductive agent, second dispersant and second binder are used. Through the combination and structural design of these coatings, the flexibility, compaction density and electronic conductivity of the negative electrode sheet are improved.
It improves the flexibility, compaction density and electronic conductivity of the negative electrode sheet, reduces the risk of sodium analysis and the probability of powder loss, and improves the circulation and rate performance of sodium ion batteries.
Smart Images

Figure CN119560500A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sodium ion batteries, and in particular to a negative electrode plate and a preparation method thereof, a sodium ion battery and an electrical device. Background Art
[0002] Sodium-ion batteries are a new energy storage technology that has entered the mass production stage. Because their raw materials are widely distributed around the world and have abundant reserves, and because of their excellent low-temperature performance, sodium-ion batteries can be used as a powerful supplement to lithium-ion batteries. At present, the main material for the negative electrode of sodium-ion batteries is hard carbon. It has the advantages of high capacity, good rate performance, and small volume expansion. However, its amorphous microstructure makes it have higher mechanical strength and lower electronic conductivity than graphite and soft carbon. These characteristics make the negative electrode of sodium-ion batteries with hard carbon as the main active material have the following process problems:
[0003] 1) The high mechanical strength of hard carbon makes it difficult to fill the gaps in the pole piece during the rolling process, making it difficult to increase the compaction density of the pole piece. In addition, if the compaction density of the pole piece is forcibly increased, a greater rolling pressure must be applied, which may damage the structure of the adhesive in the dressing and reduce its adhesion, thereby causing a decrease in the peeling force of the pole piece;
[0004] 2) The inherent low electronic conductivity of hard carbon and the high contact impedance caused by the large number of internal voids after the pole piece is rolled make the overall electronic conductivity of the pole piece low;
[0005] 3) The conductive agent in the prior art easily causes the negative electrode of the electrode to lose powder;
[0006] Therefore, there is an urgent need to provide a new negative electrode plate to solve the above problems. Summary of the invention
[0007] The purpose of the present application is to provide a negative electrode plate and a preparation method thereof, a sodium ion battery and an electrical device to solve the above-mentioned problems.
[0008] To achieve the above objectives, the present application provides, in a first aspect, a negative electrode sheet, including a current collector, a first coating layer, and a second coating layer;
[0009] The first coating is disposed between the current collector and the second coating;
[0010] The raw materials of the first coating layer include hard carbon, first soft carbon, first conductive agent, first dispersant and first binder;
[0011] The raw materials of the second coating layer include second soft carbon, a second conductive agent, a second dispersant and a second binder.
[0012] Optionally, the raw materials of the first coating, based on the total mass of 100%, include: 80%-90% of the hard carbon, 2%-15% of the first soft carbon, 1%-5% of the first conductive agent, 1%-2% of the first dispersant, and 1%-3.5% of the first binder.
[0013] Optionally, the raw materials of the second coating layer, calculated based on the total mass as 100%, include: 92%-97% of the second soft carbon, 1%-5% of the second conductive agent, 1%-2% of the second dispersant, and 1%-3.5% of the second binder.
[0014] Optionally, the negative electrode plate satisfies at least one of the following conditions:
[0015] A. The thickness of the first coating is 30 μm-200 μm;
[0016] B. The thickness of the second coating is 3%-20% of the thickness of the first coating;
[0017] C. The thickness of the current collector is 5 μm-20 μm.
[0018] Optionally, the negative electrode plate satisfies at least one of the following conditions:
[0019] A. The precursor of the hard carbon includes one or more of biomass, resin, coal-based asphalt, and organic polymer;
[0020] B. The D50 of the hard carbon is 2 μm-10 μm.
[0021] Optionally, the negative electrode plate satisfies at least one of the following conditions:
[0022] A. The precursors of the first soft carbon and the second soft carbon are independently one or more of coal, asphalt, and petroleum coke;
[0023] B. D50 of the first soft carbon and the second soft carbon are each independently 2 μm to 10 μm.
[0024] Optionally, the negative electrode plate satisfies at least one of the following conditions:
[0025] A. The first conductive agent and the second conductive agent are independently one or more of conductive graphite, conductive carbon black, and carbon nanotubes;
[0026] B. the first dispersant and the second dispersant each independently comprise CMC;
[0027] C. the first binder and the second binder are each independently SBR and / or PAA;
[0028] D. The current collector includes aluminum foil and / or copper foil.
[0029] The second aspect of the present application provides a method for preparing the negative electrode sheet, comprising:
[0030] The raw materials of the first coating layer and the second coating layer are used to obtain a first coating layer slurry and a second coating layer slurry respectively;
[0031] The first coating slurry and the second coating slurry are sequentially disposed on the surface of the current collector to obtain the negative electrode sheet.
[0032] A third aspect of the present application provides a sodium ion battery, comprising the negative electrode sheet or the negative electrode sheet prepared by the method for preparing the negative electrode sheet.
[0033] A fourth aspect of the present application provides an electrical device, comprising the sodium ion battery.
[0034] Compared with the prior art, the beneficial effects of this application include:
[0035] The negative electrode plate provided by the present application is based on the addition of the first soft carbon and the first conductive agent in the first coating layer, so that the first coating layer and the second coating layer have higher flexibility, compaction density, electronic conductivity, cycle performance, and rate performance than the pure hard carbon layer, and can also reduce the risk of sodium precipitation and the probability of powder falling; wherein, the first soft carbon and the first conductive agent can act as solid lubricants, improve the flexibility of the negative electrode plate, greatly reduce the resistance between the hard carbon particles, and make the hard carbon particles rearrange to a greater extent during the rolling process, thereby reducing the gaps between the particles and improving the compaction density of the plate.
[0036] The method for preparing the negative electrode plate provided in the present application has high processing efficiency and low production cost.
[0037] The sodium ion battery and electrical equipment provided in this application have excellent electrochemical performance, long service life and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0039] Figure 1 Schematic diagram of the negative electrode provided in this application.
[0040] Description of main component symbols:
[0041] 100 - current collector; 200 - first coating layer; 300 - second coating layer. DETAILED DESCRIPTION
[0042] As used herein:
[0043] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0044] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0045] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0046] In these examples, parts and percentages are by mass unless otherwise indicated.
[0047] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0048] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0049] In a first aspect, the present application provides a negative electrode sheet, including a current collector, a first coating layer, and a second coating layer;
[0050] The first coating is disposed between the current collector and the second coating;
[0051] The raw materials of the first coating layer include hard carbon, first soft carbon, first conductive agent, first dispersant and first binder;
[0052] The raw materials of the second coating layer include second soft carbon, a second conductive agent, a second dispersant and a second binder.
[0053] It should be noted that the structures of the first coating and the second coating are interdependent, and the raw materials and proportions of each coating have an influence that cannot be ignored on the corresponding coating and the non-corresponding coating. It can be understood that when there is only the first coating and no second coating, since the main raw material of the first coating is hard carbon, it has the characteristics of high mechanical strength, low true density, more polar functional groups, but high specific capacity. This makes high-capacity hard carbon the choice for sodium-ion batteries that require high energy density. However, due to its high mechanical strength, there are two disadvantages in the rolling process of the pole piece. One is that the rearrangement of the particles is more difficult, and the gaps between the particles cannot be fully filled; the second is that the mechanical force between the particles is large, which causes certain structural damage to the binder. These two disadvantages result in low compaction density of the pole piece, low peeling force of the pole piece, and easy detachment of the particles. The detached particles will increase the risk of battery short circuit. The low true density of hard carbon is also a factor that affects the improvement of the compaction density of the pole piece; in addition, hard carbon contains more polar functional groups, which makes it relatively soft carbon to organic electrolytes. The affinity will be lower, which makes the battery need a longer time to allow the electrolyte to fully infiltrate the pole piece after injection, and will also cause the cycle performance to deteriorate rapidly due to the loss of electrolyte in the later stage of the cycle. Since only the first coating has the above problems, a second coating is set. The advantage of this setting is that since the main raw material of the second coating contains soft carbon, it has a higher true density than hard carbon, less functional group content, and lower mechanical strength. The low mechanical strength makes the soft carbon more easily deformed during the rolling process, the particle rearrangement process in the pole piece is more complete, the contact between the particles is closer, and the degree of damage to the binder structure by the particles is reduced, resulting in a stronger bonding effect between the particles of the second coating, which improves the compaction density of the entire pole piece and reduces the powder loss probability and short circuit rate of the entire pole piece. The true density of soft carbon is relatively higher, which also improves the compaction density of the pole piece to a certain extent; the functional group content of soft carbon is lower than that of hard carbon, which also makes the coating more liquid-retaining and slows down the rapid deterioration of battery performance due to the lack of electrolyte in the later stage of the cycle;
[0054] The advantage of disposing the second coating on the outside of the first coating (i.e., on the side close to the battery electrolyte and the diaphragm) is that the second coating can serve as a coating layer for the first coating to bind the first coating, thereby reducing the tendency of the first coating to shed powder and increase the short circuit rate caused by the shed powder. In addition, the second coating is closer to the electrolyte, which can increase the ability of the electrode to absorb and retain the electrolyte.
[0055] In some embodiments, the raw materials of the first coating, based on the total mass of 100%, include: 80%-90% of the hard carbon, 2%-15% of the first soft carbon, 1%-5% of the first conductive agent, 1%-2% of the first dispersant, and 1%-3.5% of the first binder.
[0056] Optionally, based on the total mass of the raw materials for the first coating being 100%, the hard carbon may be 80%, 82%, 84%, 86%, 88%, 90% or any value between 80% and 90%, the first soft carbon may be 2%, 3%, 6%, 9%, 12%, 15% or any value between 2% and 15%, the first conductive agent may be 1%, 2%, 3%, 4%, 5% or any value between 1% and 5%, the first dispersant may be 1%, 1.5%, 2% or any value between 1% and 2%, and the binder may be 1%, 2%, 3%, 3.5% or any value between 1% and 3.5%.
[0057] It should be noted that soft carbon provides relatively less capacity than hard carbon, while other substances such as conductive agents increase conductivity, dispersants increase dispersion stability, and binders play a connecting role. Therefore, in order to increase the capacity of the negative electrode, the proportion of conductive agents, binders and dispersants will be reduced as much as possible, and the appropriate ratio will be maintained to achieve optimal performance.
[0058] In some embodiments, the raw materials of the second coating layer, based on the total mass of 100%, include: 92%-97% of the second soft carbon, 1%-5% of the second conductive agent, 1%-2% of the second dispersant, and 1%-3.5% of the second binder.
[0059] Optionally, based on the total mass of the raw materials for the second coating being 100%, the second soft carbon may be 92%, 93%, 94%, 95%, 96%, 97% or any value between 92% and 97%, the second conductive agent may be 1%, 2%, 3%, 4%, 5% or any value between 1% and 5%, the second dispersant may be 1%, 1.5%, 2% or any value between 1% and 2%, and the second binder may be 1%, 2%, 3%, 3.5% or any value between 1% and 3.5%.
[0060] In some embodiments, the negative electrode plate satisfies at least one of the following conditions:
[0061] A. The thickness of the first coating is 30 μm-200 μm;
[0062] Optionally, the thickness of the first coating layer may be 30 μm, 50 μm, 100 μm, 150 μm, 200 μm, or any value between 30 μm and 200 μm;
[0063] B. The thickness of the second coating is 3%-20% of the thickness of the first coating;
[0064] Optionally, the thickness of the second coating layer may be 3%, 5%, 10%, 15%, 20% or any value between 3% and 20% of the thickness of the first coating layer;
[0065] It should be noted that the second coating is mainly soft carbon, which is characterized by low capacity but good rate performance; therefore, with energy density as the main indicator, the thickness of the first layer is set wider; with rate performance as the main indicator, the second layer is coated thicker. When the thickness of the second coating can be less than 3% of the thickness of the first coating, the thickness of the second coating will be difficult to control; when the thickness of the second coating can be greater than 20% of the thickness of the first coating, the proportion of soft carbon in the negative electrode is too high, which will result in a very low energy density of the sodium battery;
[0066] C. The thickness of the current collector is 5 μm-20 μm.
[0067] Optionally, the thickness of the current collector may be 5 μm, 10 μm, 15 μm, 20 μm or any value between 5 μm and 20 μm.
[0068] In some embodiments, the negative electrode plate satisfies at least one of the following conditions:
[0069] A. The precursor of the hard carbon includes one or more of biomass, resin, coal-based asphalt, and organic polymer;
[0070] B. The D50 of the hard carbon is 2 μm-10 μm.
[0071] Optionally, the D50 of the hard carbon may be 2 μm, 4 μm, 6 μm, 8 μm, 10 μm or any value between 2 μm and 10 μm.
[0072] It should be noted that particles with a small D50 have the advantage of good kinetic performance, but also have the disadvantage of reducing the first efficiency of the sodium-ion full battery; particles with a large D50 have the advantage of high first efficiency of the sodium-ion full battery, but have the disadvantage of poor kinetic performance. Therefore, when the D50 of hard carbon is 2μm-10μm, the effect is best.
[0073] In some embodiments, the negative electrode plate satisfies at least one of the following conditions:
[0074] A. The precursors of the first soft carbon and the second soft carbon are independently one or more of coal, asphalt, and petroleum coke;
[0075] B. D50 of the first soft carbon and the second soft carbon are each independently 2 μm to 10 μm.
[0076] Optionally, D50 of the first soft carbon and the second soft carbon may be independently 2 μm, 4 μm, 6 μm, 8 μm, 10 μm or any value between 2 μm and 10 μm.
[0077] In some embodiments, the negative electrode plate satisfies at least one of the following conditions:
[0078] A. The first conductive agent and the second conductive agent are independently one or more of conductive graphite, conductive carbon black, and carbon nanotubes;
[0079] In some specific embodiments, conductive graphite or a mixture of conductive graphite and other conductive agents is preferably selected, because the negative electrode sheet after adding conductive graphite has the following beneficial effects:
[0080] 1. High flexibility; the first soft carbon and conductive graphite have higher crystallinity than hard carbon, and the van der Waals force between soft carbon and conductive graphite sheets is weaker, which makes the soft carbon and conductive graphite easier to deform under the action of external force. When the pole piece is bent, the particles in the dressing layer of the pole piece will have interaction forces with each other. The first soft carbon and conductive graphite can act as solid lubricants to improve the flexibility of the negative pole piece. The second coating is arranged on the surface of the first coating and is composed of the second soft carbon. After being subjected to force, it will also avoid cracking of the coating or even breaking of the negative pole piece because its deformation ability is higher than that of hard carbon.
[0081] 2. It has a higher compaction density. First, soft carbon and conductive graphite act as lubricants, which can greatly reduce the resistance between hard carbon particles during rolling, and make the hard carbon particles rearrange to a greater extent during rolling, thereby reducing the gaps between particles and improving the compaction density of the pole piece. Second, the internal gaps of soft carbon are less, and the true density is greater than that of hard carbon. The second coating can also increase the compaction density of the negative pole piece.
[0082] 3. It has high electronic conductivity; the addition of the first soft carbon and conductive graphite replaces part of the hard carbon, thereby improving the electronic conductivity of the electrode, the second coating has a high proportion of soft carbon, and no hard carbon is set, and the setting of the second coating improves the overall conductivity of the negative electrode; in addition, the compaction density of the negative electrode of the present application is improved, the internal pores of the negative electrode are reduced, and the contact area between the particles is increased, which will increase the conductive path of the electrons and thus improve the electronic conductivity of the electrode;
[0083] 4. It can improve the manufacturing efficiency of the battery; the polar functional groups of conductive graphite, soft carbon and hard carbon gradually increase, the hydrophilicity gradually increases, and the lipophilicity gradually decreases. Therefore, replacing part of the hard carbon with soft carbon and conductive graphite can increase the electrolyte absorption rate of the electrode; the second coating is mainly composed of soft carbon, and the second coating is located on the surface of the negative electrode. Compared with the electrode without the second coating, such a structure can make the electrolyte quickly absorbed when it contacts the negative electrode. Since the rate of electrolyte absorption by the negative electrode increases, the static time after injection can be reduced during the battery manufacturing process, thereby improving the processing efficiency and reducing the manufacturing cost;
[0084] 5. Improve the cycle performance of the battery; usually, the capacity decay in the later stage of the cycle is caused by the lack of electrolyte. The lipophilicity of conductive graphite and soft carbon is higher than that of hard carbon, that is, the combination of the two with the electrolyte is tighter, which can improve the ability of the negative electrode to retain the electrolyte. Therefore, the present application can improve the electrolyte retention capacity and avoid the rapid decay of battery life due to the drying of the electrolyte in the later stage of the battery cycle;
[0085] 6. Improve the rate performance of the battery; soft carbon has a large proportion of slope capacity, and the sodium storage mechanism of the slope section is adsorption. The kinetic performance of this sodium storage mechanism is good. Adding soft carbon to the first coating can improve the ionic conductivity of the negative electrode sheet compared to the electrode sheet without soft carbon. The second coating is located on the surface of the negative electrode sheet, and it is mainly composed of soft carbon. During the charge and discharge process, due to its largest contact surface with the electrolyte, the sodium ions can be quickly embedded and removed through the adsorption of soft carbon on sodium ions during the charge and discharge process, so as to improve the rate performance of the battery;
[0086] 7. Reduce the risk of sodium precipitation in the battery; soft carbon has almost no platform capacity below 0.1V. The present application mixes soft carbon in the first coating layer and mainly uses soft carbon in the second coating layer, which will increase the overall use ratio of soft carbon, so that the potential of the negative electrode sheet can be increased, thereby reducing the risk of sodium precipitation of the battery during high-rate charging and low-temperature charging;
[0087] 8. Reduce the probability of powder falling from the pole piece, the self-discharge tendency of the battery and the short-circuit rate; for conventional SP conductive agents, the particle size is only about 40nm, which means that the number of uniformly dispersed SP particles will be very large. Under the action of a certain amount of negative electrode binder, it is inevitable that many particles will be subject to a small bonding force and easily fall off the pole piece, thereby increasing the probability of powder falling from the pole piece, and these falling powders will increase the probability of short circuit or self-discharge of the battery;
[0088] In some specific embodiments, when a mixture of conductive graphite, conductive carbon black and carbon nanotubes is selected, since the particle size of conductive graphite is larger than that of conductive carbon black (CNT conductive agent is linear, generally not referring to particle size; conductive graphite and conductive carbon black are block-shaped, generally describing their size by particle size), therefore, the amount of conductive graphite can be appropriately increased, which can reduce the probability of powder falling off of the negative electrode plate, thereby reducing the short circuit rate and physical self-discharge degree of the battery. Exemplarily, the raw materials of the first conductive agent or the second conductive agent are calculated by total mass as 100%, including: 60%-100% of conductive graphite, 0%-10% of conductive carbon black, and 0%-30% of carbon nanotubes;
[0089] B. the first dispersant and the second dispersant each independently comprise CMC;
[0090] C. the first binder and the second binder are each independently SBR and / or PAA;
[0091] D. The current collector includes aluminum foil and / or copper foil.
[0092] The second aspect of the present application provides a method for preparing the negative electrode sheet, comprising:
[0093] The raw materials of the first coating layer and the second coating layer are used to obtain a first coating layer slurry and a second coating layer slurry respectively;
[0094] The first coating slurry and the second coating slurry are sequentially disposed on the surface of the current collector to obtain the negative electrode sheet.
[0095] In some specific embodiments, the first coating layer and the second coating layer may be disposed on a single side of the current collector.
[0096] In some specific embodiments, the first coating and the second coating may be disposed on both sides of the current collector, for example, Figure 1 As shown, the first coating layer 200 and the second coating layer 300 are disposed on both sides of the current collector 100 .
[0097] A third aspect of the present application provides a sodium ion battery, comprising the negative electrode sheet or the negative electrode sheet prepared by the method for preparing the negative electrode sheet.
[0098] In some specific embodiments, the sodium ion battery includes, in addition to the negative electrode plate, a positive electrode plate, a separator and an electrolyte.
[0099] Among them, the positive electrode plate, separator and electrolyte can adopt any commercially available positive electrode plate, separator and electrolyte, or the positive electrode plate, separator and electrolyte made according to any existing technology, and this application does not limit this.
[0100] A fourth aspect of the present application provides an electrical device, comprising the sodium ion battery.
[0101] It should be noted that electrical equipment may be but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc.; among them, mobile devices may include but are not limited to at least one of mobile phones, laptop computers, etc.; electric vehicles may include but are not limited to at least one of pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0102] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0103] Example 1
[0104] In a first aspect, the present embodiment provides a negative electrode sheet, including a current collector, a first coating layer and a second coating layer, wherein the first coating layer is disposed between the current collector and the second coating layer;
[0105] The raw materials of the first coating layer are calculated based on the total mass of 100%, including: 84% of hard carbon, 10% of first soft carbon, 2.5% of first conductive agent (1.5% of conductive graphite and 1% of carbon nanotubes), 1% of first dispersant CMC, and 2.5% of binder;
[0106] The raw materials of the second coating layer, calculated based on the total mass of 100%, include: 94% of second soft carbon, 2.5% of second conductive agent (1.5% of conductive graphite and 1% of carbon nanotubes), 1% of second dispersant CMC, and 2.5% of second binder.
[0107] The thickness of the first coating layer is 80 μm, the thickness of the second coating layer is 12 μm, and the thickness of the current collector is 12 μm.
[0108] The precursor of the hard carbon is coconut shell, and D50 is 6 μm; the precursors of the first soft carbon and the second soft carbon are both asphalt, and D50 is both 6 μm; the first binder and the second binder are both SBR; and the current collector is aluminum foil.
[0109] A second aspect of this embodiment provides a method for preparing a negative electrode sheet, comprising:
[0110] The raw materials of the first coating layer and the second coating layer are mixed respectively to obtain a first coating layer slurry and a second coating layer slurry;
[0111] The first coating slurry is applied to both sides of the current collector and dried to obtain a first coating layer, and then the second coating slurry is applied to the surface of the first coating layer and dried to obtain a negative electrode sheet.
[0112] The schematic diagram of the structure of the negative electrode is as follows Figure 1 shown.
[0113] A third aspect of the present embodiment provides a sodium ion battery, comprising the above-mentioned negative electrode sheet, positive electrode sheet, separator and electrolyte;
[0114] Among them, the O3-type layered oxide positive electrode accounts for 95% of the positive electrode, CNT accounts for 1%, SP accounts for 2.5, and PVDF5130 accounts for 1.5%;
[0115] The diaphragm is a 12μm PE layer + 4μm ceramic coating;
[0116] The electrolyte is 1M NaPF6, EC-DMC system.
[0117] Example 2
[0118] The difference from Example 1 is that the hard carbon in the raw material of the first coating accounts for 89% and the first soft carbon accounts for 5%.
[0119] Example 3
[0120] The difference from Example 1 is that the hard carbon in the raw material of the first coating layer accounts for 80% and the first soft carbon accounts for 14%.
[0121] Comparative Example 1
[0122] The difference from Example 1 is that only a single layer of coating with a thickness of 100 μm is provided on both sides of the current collector, and the raw materials of the coating, calculated based on the total mass as 100%, include: 94% hard carbon, 2% conductive carbon black, 0.5% carbon nanotubes, 1% dispersant, and 2.5% binder.
[0123] Comparative Example 2
[0124] The difference from Comparative Example 1 is that no carbon nanotubes are provided and the conductive carbon black is 2.5%.
[0125] Comparative Example 3
[0126] The difference from Example 1 is that the positions of the first coating layer and the second coating layer are replaced.
[0127] Comparative Example 4
[0128] The difference from Example 1 is that the thickness of the first coating layer and the second coating layer are both 45 μm.
[0129] Comparative Example 5
[0130] The difference from Example 1 is that only the first coating layer is provided.
[0131] Comparative Example 6
[0132] The difference from Example 1 is that only the second coating layer is provided.
[0133] Comparative Example 7
[0134] The difference from Example 1 is that the raw materials of the first coating, calculated based on the total mass of 100%, include: hard carbon 95.5%, first soft carbon 0%, SP 0.75%, first dispersant 3%, and binder 0.75%.
[0135] Comparative Example 8
[0136] The difference from Example 1 is that the raw materials of the second coating, calculated based on the total mass of 100%, include: 80% of second soft carbon, 10% of second conductive agent, 5% of second dispersant, and 5% of second binder.
[0137] The negative electrode sheets and sodium ion batteries prepared in the above embodiments and comparative examples were subjected to electrochemical performance tests, including compaction density, flexibility performance test, powder loss test, sheet resistivity and energy density. The specific test results are shown in Table 1.
[0138] Among them, compaction density: Equipment used: roller pressing equipment; Equipment parameters: Rolling pressure is generally 3MPa-15MPa; Calculation method: The coating surface density of the pole piece after rolling divided by the coating thickness. Rating standard: 1.0g / cm 3 -0.95g / cm 3 a, 0.95 g / cm 3 -0.9g / cm 3 b, and so on, each interval is 0.05g / cm 3 For the first level.
[0139] Flexibility performance test: Equipment used: manual folding; Test method: Take the electrode after rolling, fold it in half manually, and observe whether the collector leaks; Rating standard: If the foil leaks after folding once, it is rated as poor flexibility; if the foil leaks after folding 2-3 times, it is rated as average flexibility; if the foil leaks after folding more than 3 times, it is rated as good flexibility.
[0140] Powder drop test: Equipment used: Fold the pole piece in half manually, and weigh the mass of powder falling off the pole piece with a balance. Test method: Fold the pole piece in half 5 times manually, and weigh the mass of powder falling off the pole piece. Rating standard: Below 0.1mg, rated as very little; between 0.1mg-0.5mg, rated as little; 0.5mg-1mg rated as more; between 1mg-5mg, rated as much; above 5mg, rated as a lot.
[0141] Pole sheet resistivity: Equipment used: Pole sheet resistance meter 2300; Test parameters: Test pressure 26.26MPa, test area 153.94mm 2 , the instrument will directly display the resistivity value of the electrode. Rating standard: below 0.1Ωcm, rating is b.
[0142] Energy density: The 0.2C discharge energy of the battery, divided by the mass of the battery, gives the mass energy density of the battery. Rating standard: The energy density of soft-pack batteries is rated A at 120-115Wh / kg; B at 125-120Wh / kg; and C at 115-110Wh / kg.
[0143] Table 1 Electrochemical performance test
[0144] Test components Compacted density Flexible properties Fan loss Electrode sheet resistivity Energy density Example 1 a good Very rare b A Example 2 a good Very rare b B Example 3 a good Very rare b C Comparative Example 1 0.95a generally More 1.1b 1.05A Comparative Example 2 0.95a generally More 1.12b 1.03A Comparative Example 3 a good few b A Comparative Example 4 a good Very rare 0.95b 0.7A Comparative Example 5 0.97a good few 1.01b 1.05A Comparative Example 6 1.1a good Very rare 0.90b 0.3A Comparative Example 7 0.9a Difference a lot of 1.1b 1.05A Comparative Example 8 0.99a generally Very rare 0.95b 0.99A
[0145] analyze:
[0146] It can be seen from Table 1 that for Examples 1-3, the compaction density of the pole piece can be set at the same level. Due to the addition of conductive graphite and soft carbon, the flexibility of the pole piece is improved, so the flexibility of the three embodiments is good. Due to the formula design and structural design of the pole piece, the tendency of the pole piece to lose powder is greatly reduced, and the powder loss in the three embodiments is very small. Due to the increase in compaction density, the contact between particles is close, and the resistivity of the pole piece is very low, basically below 0.1Ωcm. Since Example 2 has the highest hard carbon content, Example 3 has the lowest hard carbon content, and Example 1 has a medium hard carbon content, the energy density of the three is basically positively correlated with the hard carbon content.
[0147] For Comparative Example 1, the difference between it and Example 1 is that only a single layer of coating is set on both sides of the current collector, and the mass of hard carbon accounts for 94%, conductive carbon black accounts for 2%, carbon nanotubes accounts for 0.5%, dispersant accounts for 1%, and binder accounts for 2.5%. There is no soft carbon, graphite-type conductive agent, and second coating in this formula, which makes it difficult to make the compaction density of this comparative example very high, only 0.95 times that of Example 1. And because there are no easily deformed materials such as soft carbon and graphite, its flexibility is also poor. And because the conductive carbon black with a very small particle size accounts for a relatively large proportion of 2%, and the binder of hard carbon is damaged during the rolling process, the adhesion of the pole piece is low and more powder falls off. And because the compaction density is difficult to increase and the gaps between the particles are large, the resistivity of the pole piece is also increased relative to Example 1. However, due to the large proportion of hard carbon, its energy density is improved to a certain extent relative to Example 1.
[0148] For Comparative Example 2, relative to Comparative Example 1, only 0.5% of CNT is replaced with 0.5% conductive carbon black; therefore, if the compaction of Comparative Example 2 is set to the same value as that of Comparative Example 1, the flexibility of both is average, and the powder loss situation is not improved, and both are relatively large. The resistivity of the pole piece of Comparative Example 2 will increase slightly. This is because CNT is generally more conductive than conductive carbon black, and replacing CNT with conductive carbon black will reduce the conductivity of the pole piece to a certain extent. In addition, the energy density of Comparative Example 2 will decrease slightly relative to Comparative Example 1. This is because the resistance of the battery increases, which increases the kinetic loss of the battery.
[0149] For Comparative Example 3, the only difference between it and Example 1 is that the first coating and the second coating are swapped, so its compaction, flexibility, pole piece resistivity and energy density are almost the same. However, since the first coating is adjusted to the outside of the second coating (away from the current collector is called the outside), since the main raw material of the first coating is hard carbon, it has some damage to the binder, and the gaps between the particles after rolling are also more than those of the second coating, so in general, the particles on the first coating are more likely to fall off from the pole piece, so the powder loss of Comparative Example 3 is slightly more serious than that of Example 1.
[0150] For Comparative Example 4, the difference between it and Example 1 is the thickness of the pole piece, and the thickness of the second coating is the same as the thickness of the first coating. Similarly, the compaction density of Comparative Example 4 can be set to the same value as that of Example 1. Comparative Example 4 is similar to Example 1, and its pole piece has good flexibility and very little powder loss; however, since the proportion of soft carbon is higher than that of Example 1, its pole piece resistivity is reduced to a certain extent. And since the proportion of hard carbon is reduced relative to Example 1, the energy density of the battery is reduced to a certain extent.
[0151] For Comparative Example 5, since only the first coating of Example 1 is set, its compaction density may be slightly lower than that of Example 1 because there is no second coating. The soft carbon of the second coating, in addition to having a slightly higher true density than hard carbon, is easy to deform when subjected to external force, which also makes the second coating denser. Therefore, overall, the compaction density of Example 1 is slightly higher. The flexibility of Comparative Example 5 is basically the same as that of Example 1; due to the loss of the restraint of the second coating, the powder loss of the pole piece will be more serious than that of Example 1. However, since the second coating with soft carbon as the main raw material is removed, the proportion of hard carbon increases, which slightly improves the energy density of the battery.
[0152] For Comparative Example 6, since it only has the second coating layer compared to Example 1, the compaction density of the pole piece is improved. It has good flexibility and very little powder loss. Due to the compactness of the second coating layer and the better conductivity of soft carbon than hard carbon, the resistivity of the pole piece is reduced; however, since the first coating layer with hard carbon as the main raw material is removed, its energy density is significantly reduced.
[0153] For Comparative Example 7, the changes relative to Example 1 come from the formula of the first coating, which sets SP to 0.75% and the binder to 0.75%. Compared with Example 1, since the first coating lacks soft carbon and graphite, two substances that are easier to deform than hard carbon, the particle rearrangement during the rolling process will not be too sufficient, resulting in a decrease in compaction density. And due to the increase in the CMC content, the flexibility of the pole piece is significantly reduced. And due to the significant reduction in the binder content, the pole piece loses a lot of powder. The reduction in the conductive agent content and the reduction in the density of the pole piece increase the resistivity of the pole piece. Due to the increase in the proportion of hard carbon, the energy density is slightly improved.
[0154] For Comparative Example 8, since the second dispersant and the second binder are significantly improved compared with Example 1, the true density of the dispersant and the binder is lower than that of soft carbon, so the compaction density is slightly reduced. Since the content of the dispersant CMC is relatively high, the brittleness of this dispersant is relatively large, which will cause the brittleness of the pole piece to increase compared with Example 1, so the flexibility is average. Since the content of the binder is relatively high, the powder shedding of the pole piece is also very rare. Although the conductive agent content of the second coating is significantly increased, the proportion of the binder, a basically non-conductive material, is also increased. Therefore, the conductivity of the pole piece is improved to a certain extent, and its resistivity is reduced. Due to the reduction of active substances such as soft carbon, the energy density of the battery is reduced compared with Example 1.
[0155] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0156] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A negative electrode plate, characterized in that: comprising a current collector, a first coating layer, and a second coating layer; The first coating is disposed between the current collector and the second coating; The raw materials of the first coating layer include hard carbon, first soft carbon, first conductive agent, first dispersant and first binder; The raw materials of the second coating layer include second soft carbon, a second conductive agent, a second dispersant and a second binder.
2. The negative electrode sheet according to claim 1, characterized in that: The raw materials of the first coating layer include, based on a total mass of 100%, 80%-90% of the hard carbon, 2%-15% of the first soft carbon, 1%-5% of the first conductive agent, 1%-2% of the first dispersant, and 1%-3.5% of the binder.
3. The negative electrode sheet according to claim 1, characterized in that: The raw materials of the second coating layer, calculated based on the total mass of 100%, include: 92%-97% of the second soft carbon, 1%-5% of the second conductive agent, 1%-2% of the second dispersant, and 1%-3.5% of the second binder.
4. The negative electrode sheet according to claim 1, characterized in that: At least one of the following conditions is met: A. The thickness of the first coating is 30 μm-200 μm; B. The thickness of the second coating is 3%-20% of the thickness of the first coating; C. The thickness of the current collector is 5 μm-20 μm.
5. The negative electrode sheet according to claim 1, characterized in that: At least one of the following conditions is met: A. The precursor of the hard carbon includes one or more of biomass, resin, coal-based asphalt, and organic polymer; B. The D50 of the hard carbon is 2 μm-10 μm.
6. The negative electrode sheet according to claim 1, characterized in that: At least one of the following conditions is met: A. The precursors of the first soft carbon and the second soft carbon are independently one or more of coal, asphalt, and petroleum coke; B. D50 of the first soft carbon and the second soft carbon are each independently 2 μm to 10 μm.
7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that: At least one of the following conditions is met: A. The first conductive agent and the second conductive agent are independently one or more of conductive graphite, conductive carbon black, and carbon nanotubes; B. the first dispersant and the second dispersant each independently comprise CMC; C. the first binder and the second binder are each independently SBR and / or PAA; D. The current collector includes aluminum foil and / or copper foil.
8. A method for preparing a negative electrode sheet according to any one of claims 1 to 7, characterized in that: include: The raw materials of the first coating layer and the second coating layer are used to obtain a first coating layer slurry and a second coating layer slurry respectively; The first coating slurry and the second coating slurry are sequentially disposed on the surface of the current collector to obtain the negative electrode sheet.
9. A sodium ion battery, characterized in that: The negative electrode sheet comprises the negative electrode sheet according to any one of claims 1 to 7 or the negative electrode sheet prepared by the preparation method of the negative electrode sheet according to claim 8.
10. An electrical device, characterized in that: Including the sodium ion battery as described in claim 9.
Citation Information
Cited By
Negative pole piece and sodium ion battery
CN121097017A
Negative pole piece of sodium ion battery, preparation method of negative pole piece and sodium ion battery
CN121306927A
Functional aluminum foil for improving powder falling of hard carbon negative electrode, preparation method of functional aluminum foil, sodium-ion battery and electric device
CN121355267A